2013
DOI: 10.1155/2013/835956
|View full text |Cite
|
Sign up to set email alerts
|

Protumor Activities of the Immune Response: Insights in the Mechanisms of Immunological Shift, Oncotraining, and Oncopromotion

Abstract: Experimental and clinical studies indicate that cells of the innate and adaptive immune system have both anti- and pro-tumor activities. This dual role of the immune system has led to a conceptual shift in the role of the immune system's regulation of cancer, in which immune-tumor cell interactions are understood as a dynamic process that comprises at least five phases: immunosurveillance, immunoselection, immunoescape, oncotraining, and oncopromotion. The tumor microenvironment shifts immune cells to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 164 publications
0
62
0
Order By: Relevance
“…Depending on the dominant cellular subtypes, protumor or antitumor effects are expected . M2 macrophages, regulatory T cells, and N2 neutrophils have been considered to have protumor activity . Both granulocytic lineage MDSCs and TANs have gained much more relevance recently and, because of the similarities of their protumoral and phenotypic characteristics, their distinction has not been simple .…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the dominant cellular subtypes, protumor or antitumor effects are expected . M2 macrophages, regulatory T cells, and N2 neutrophils have been considered to have protumor activity . Both granulocytic lineage MDSCs and TANs have gained much more relevance recently and, because of the similarities of their protumoral and phenotypic characteristics, their distinction has not been simple .…”
Section: Discussionmentioning
confidence: 99%
“…Both experimental and clinical studies have shown that the tumor microenvironment shifts Ma and other immune cells to perform functions related to the tumor’s needs (oncotraining). These functions are related to chronic inflammation and tissue remodeling and include increased proliferation and survival, increased angiogenesis and vessel permeability, and self-renewal properties that together promote tumor growth and metastasis [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…All stromal cells participate in the progression of the tumor, probably providing direct cell to cell and cell to ECM interactions, and from the soluble factors they secrete. Tumors are actively recruiting immune cells; however, tumor-associated immune cells often lack immunosurveillance activities, and instead they fulfill protumoral functions (for a comprehensive review see [43]). How tumors favor this immunological switch is not completely understood.…”
Section: Discussionmentioning
confidence: 99%